2012
DOI: 10.1021/sb300047u
|View full text |Cite
|
Sign up to set email alerts
|

Functional Display of Complex Cellulosomes on the Yeast Surface via Adaptive Assembly

Abstract: A new adaptive strategy was developed for the ex vivo assembly of a functional tetravalent designer cellulosome on the yeast cell surface. The design is based on the use of (1) a surface-bound anchoring scaffoldin composed of two divergent cohesin domains, (2) two dockerin-tagged adaptor scaffoldins to amplify the number of enzyme loading sites based on the specific dockerin−cohesin interaction with the anchoring scaffoldin, and (3) two dockerin-tagged enzymatic subunits (the endoglucanse Gt and the β-glucosid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 36 publications
0
73
0
Order By: Relevance
“…Hypothetical highly engineered cell for one-pot biotransformation of lignocellulosic feedstock into liquid fuels [83]. The cellulosome scheme is based in the recently published functional display of complex cellulosomes on the yeast surface [89]. The furfural resistance by reducing cofactors was taken from the model proposed for the engineered E. coli tolerant to furfural [90].…”
Section: Discussionmentioning
confidence: 99%
“…Hypothetical highly engineered cell for one-pot biotransformation of lignocellulosic feedstock into liquid fuels [83]. The cellulosome scheme is based in the recently published functional display of complex cellulosomes on the yeast surface [89]. The furfural resistance by reducing cofactors was taken from the model proposed for the engineered E. coli tolerant to furfural [90].…”
Section: Discussionmentioning
confidence: 99%
“…Using this approach, ethanol production was increased by up to three-fold (Goyal et al, 2011). This laboratory subsequently constructed a tetravalent cellulosome using a natural adaptive assembly strategy (Tsai et al, 2013). Yeast cells displaying the tetravalent celluosome demonstrated a 2-fold increase in ethanol production compared with cells displaying a divalent cellulosome using a similar enzyme loading level (Tsai et al, 2013).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…This laboratory subsequently constructed a tetravalent cellulosome using a natural adaptive assembly strategy (Tsai et al, 2013). Yeast cells displaying the tetravalent celluosome demonstrated a 2-fold increase in ethanol production compared with cells displaying a divalent cellulosome using a similar enzyme loading level (Tsai et al, 2013). These results suggested that enzyme proximity was more important for cellulosomal synergy than simply increasing the amount of enzyme loaded on the cell surface.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Tsai et al (2010) optimized the mixing ratio of different populations and constructed a synthetic consortium expressing different components of cellulosomes for the conversion of amorphous (phosphoric Table 1 Fierobe et al (2001) acid-swollen) cellulose to ethanol with 93 % of maximum theoretical yield. A 4.2-fold increase in the hydrolysis of phosphoric acid-swollen cellulose (PASC) was reported with a tetravalent cellulosome expressed on the surface of the yeast cell as compared to the free enzymes (Tsai et al 2013). Ito et al (2009) developed recombinant yeast having a designer minicellulosome system displayed on its surface by assembling different components of the cellulosomal system C. cellulovorans, T. reesei and A. aculeatus for the hydrolysis of β-glucan.…”
Section: Alternative-designer Cellulosomesmentioning
confidence: 99%